Code-Switching in a University EMI Classroom: Patterns and Implications - Susilowaty, Susilowaty; Rosa, R.A. Angelica Sherly (English Education : English Journal for Teaching and Learning, 2024)
English as a medium of instruction (EMI) has been encouraged to be used in higher education in Indonesia. However, there has been a challenge in which the students cannot fully comprehend the content of the course. As a result, lecturers frequently do code-switching (CS) during their teaching. This case study intended to investigate the types and functions of CS that a lecturer used during her teaching in a Public Speaking class at a private university that applies EMI. A series of observation sessions and a semi-structured interview were conducted to gather the data. The findings revealed that the lecturer used situational switching more frequently than metaphorical switching when practicing CS. The study also showed that CS performed by the lecturer is able to serve particular functions that are well received by the students in the classroom, such as giving emphasis, giving examples, and showing empathy.